Attitudes towards robotisation as a predictor of the manifestation of the «uncanny valley» effect - Soroka, Aleksey A. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
It is indicated that as the degree of anthropomorphism of the robot increases, the degree of its attractiveness to humans increases, but at a certain point on the attractiveness graph the growth is replaced by a sharp decline – the «uncanny valley». It is revealed that over the last two decades a large number of studies of robotisation and the «uncanny valley» effect have been published in terms of social cybernetics, cyberpsychology, neuropsychology and zoopsychology. It was found that these studies often failed to take into account various social and psychological factors that may be important predictors of robophobia, scepticism and mistrust of robotic objects. Due to the ambiguity of definitions of the term «“uncanny valley” effect», the author’s interpretation is given: the manifestation of the «uncanny valley» effect is a process in which a robot or other object that looks or acts like a human causes rejection in human observers.